Smart Farming Adoption – A Scoping Review - Amirul Asyraf Zhahir; Mohd Ilias M Shuhud; Siti Munirah Mohd; Shafinah Kamarudin; Azuan Ahmad; Rossly Salleh; Norita MD Norwawi (KONSTELASI: Konvergensi Teknologi dan Sistem Informasi, 2024)
Smart farming, one of the most rapidly growing technologies in the agriculture sector in the midst of the Industrial Revolution 4.0 era, signifies the integration of technologies into the industry. Numerous challenges of the agriculture sector were able to be decoded and formulated efficiently. Over the past few years, research on smart farming has grown expeditiously, observing in every different cornerstone of the sector. The main objective of this study is to investigate into the smart farming technology adoption exogenous factors through the lens of a scoping review. Selections of article from several different sources, published between 2010 and 2024 with specific keywords were thoroughly observed. Valuable information was identified and discussed, particularly the positively and negatively factors influencing the adoption of smart farming. The study serves as a bedrock for an upcoming study in the smart farming technology adoption.